Vascular, type 4 Ehlers-Danlos syndrome associated with Waardenburg syndrome type 1. - Garofalo, L. (European Journal of Pediatric Dermatology, 2022)
Vascular, type 4 Ehlers-Danlos syndrome is an autosomal dominant congenital collagen disease caused by mutations in the COL3A1 gene. The latter are responsible for skin fragility, bruising, hypermobility of the limb small joints, rupture of large vessels, intestine and other organs (1). There are two variants of type 4 E-D, namely the acrogeric characterized by an aging appearance and skin fragility and the ecchymotic, characterized by easy bruising, as in the current case. Type 4 E-D is the most severe with an average survival of less than 50 years and early onset of symptoms (2). (...)